Praktik Mubāhalah di Masyarakat Desa Kajjan Kec. Blega Kab. Bangkalan-Madura - Fatichatus Sa'diyah; Maskuroh Makmun (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2022)
The history of the Prophet’s life journey once photographed a moment that was so tense when Muhammad SAW was given revelation by Allah SWT. QS. Ali Imran: 61, for inviting Najran to carry out “mubahalah” by inviting Ali, Fatima, Hasan and Husein. Mubahalah is an oath made by two disputing parties by asking Allah SWT to curse those who lie. This wes happened because the monks of Najran were reluctant to accept the truth about Prophet Isa. They believed that Jesus is the son of Allah swt. Furthermore, hundreds of years after the death of the Prophet Muhammad, the author find the practice of swearing by most of the people of Kajjan Village, Belaga District, Bangkalan Regency, in order to serve as a medium to solve very complicated problems. The author interests in studying intensely related to how the practice of oaths in the Kajjan village. The spirit of this research is living Qur’an research, which is library and field research using interview and documentation methods in data collection. The conclusion of this study is that the people of Kajjan village use practice as a medium to prove the truth of the news or quotes spoken from them, by asking Allah SWT to use the word “Billahi, Wallahi, Tallahi” if they themselves are based on a certain way